Stereospecific ligands and their complexes: Synthesis and characterization of the s-cis-K[Ru(S,S-eddp)Cl2]·3H2O - Glođović Verica V.; Trifunović Srećko R. (Journal of the Serbian Chemical Society, 2008)
In the reaction of ruthenium(III) chloride and an edda-like ligand ethylenediamine-N,N'-di-S,S-2-propionic acid (S,S-eddp) in aqueous solution led to the formation of only one of the three possible geometrical isomers potassium- s-cis-dichlorido-(ethylenediamine-N,N'-di-S,S-2-propionato)-ruthenate(III)- -trihydrate, s-cis-K[Ru(S,S-eddp)Cl2]·3H2O. The assumed geometry of the complex was based on its electronic absorption and infrared spectra.